The liberal use of magnetic resonance cholangiopancreatography can be switched over to its selective use to detect choledocholithiasis - Haji, Altaf G.; Ali M. Elhassan; Elkadi, Mahmoud; Sivakumar, Naveen; Ahmad, Aftab; Syed I. Haider; Piramanayagam, Bala; Palit, Amitabh (International Surgery Journal, 2023)
Background: Gallstone disease is known in 10-15% of adults in Western populations. Magnetic resonance cholangiopancreatography (MRCP) is the investigation of choice for choledocholithiasis; however, its use is varied, and guidelines are not well defined. The National Institute for Health and Care (NICE) guidelines recommends MRCP to be done when common bile duct (CBD) dilatation ≥8 mm or liver function tests (LFTs) are abnormal but do not quantify this further. The liberal use of MRCP is gaining popularity as a roadmap prior to cholecystectomy, aiming to assess primarily for the presence of migrated gallstones within the cystic duct or common bile duct, as well as providing information regarding the anatomical features of the extrahepatic biliary tree on an individualised basis. Due to these reasons MRCP at times is done unnecessarily which creates economic burden and restricts access to patients in real need of imaging slots. Methods: It is hospital based retrospective observational study. Time frame was July 2021 to July 2022 and sample size was 230 patients. Results: Our study showed that isolated elevated alanine aminotransferase (ALT) level should not be reason to evaluate patients for choledocholithiasis. It concluded that elevated serum bilirubin levels, alkaline phosphatase (ALP) and gamma glutamyl transferase (GGT) are the strongest predictors of CBD stones in patients with gallstone disease and hence can be used to triage patients for undergoing MRCP. Conclusions: To conclude elevated serum bilirubin levels, ALP and GGT are the strongest predictors of CBD stones in patients with gallstone disease and hence can be used to triage patients for undergoing MRCP. Isolated elevated ALT should not be a reason to evaluate patients for CBD stones.